HAMBATAN DAN PELUANG PENINGKATAN PRODUKTIVITAS PETERNAKAN KAMBING DI KABUPATEN TABANAN, PROVINSI BALI - Doloksaribu L.; I. G. N. Kayana; M. Dewantari; G. A. M. K. Dewi (Majalah Ilmiah Peternakan, 2019)
This study was undertaken to establish a database as consideration for improving goat production in TabananRegency. A survey was conducted from April to September 2018 on 38 smallholder goat farmers integrated withcommodity plantations, owning 142 goats. Data were used to measure constraints to, challenges of, and opportunitiesfor improving goat production, through a hybrid method of Strengths, Weaknesses, Opportunities and Threats andAnalytic Hierarchy Process analyses. Problem priority faced was the competition between average numbers of 2.0± 0.1 family labourers aged 38.8 ± 2.1 years who cultivated average 0.9 ± 0.1 hectare of commodity plantationsintegrated with flock size of 2.5 ± 0.2 goats per household. Goats were housed in battery systems and fed forage.About 33% farmers had just sold all or portion of their goats due to the busy activity of clove and coffee harvestingin July-September and time consuming for cut and carry forage while commercial concentrates were not given totheir goats. Recommendation taken was to providing Pennisetum purpureum silage as sustainable feed resource forgoats thus improved the nutritious content of feed particularly during dry season where feed was limited or duringharvesting and Bali Hindu ceremonies where family labourer was limited.